2014
DOI: 10.3892/mmr.2014.2639
|View full text |Cite
|
Sign up to set email alerts
|

Dual matrilineal geographic distribution of Korean type 2 diabetes mellitus-associated -11,377 G adiponectin allele

Abstract: Abstract. The present study was performed to identify the susceptible single nucleotide polymorphisms (SNPs) for the prediction of Korean type 2 diabetes mellitus (T2DM) and to clarify the matrilineal origin of Korean T2DM-specific SNPs. Fourteen SNPs from the adiponectin (ADIPOQ), hepatocyte nuclear factor 4α, phosphoenolpyruvate carboxykinase 1 and glucokinase genes in the Korean population were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…SNP −11377C/G (rs266729) demonstrated the prevalence of Korean T2D. 35 Our results have shown that adiponectin levels significantly declined in GDM with SNP −11377 C/G (rs266729) C allele. Nomani et al found that an elevated level of adiponectin was associated with the G allele of SNPs −11377 C/G (rs266729) in the Iran population.…”
Section: Discussionmentioning
confidence: 50%
“…SNP −11377C/G (rs266729) demonstrated the prevalence of Korean T2D. 35 Our results have shown that adiponectin levels significantly declined in GDM with SNP −11377 C/G (rs266729) C allele. Nomani et al found that an elevated level of adiponectin was associated with the G allele of SNPs −11377 C/G (rs266729) in the Iran population.…”
Section: Discussionmentioning
confidence: 50%
“…It has been reported that −11377 G allele might be a risk factor for type 2 diabetes among white individuals. Choi et al reported that the −11377 G allele might be responsible for T2DM incidence among Korean population . In contrast, AlSaleh et al failed to demonstrate such an association in South Asian, Southeast Asian, Black, Middle Eastern, and Far Eastern populations.…”
Section: Discussionmentioning
confidence: 98%